Coordination of Pnictogenylboranes Towards Tl(I) Salts and a Tl‐ Mediated P−P Coupling. Issue 4 (29th November 2022) - Szlosek, Robert; Ackermann, Matthias T.; Marquardt, Christian; Seidl, Michael; Timoshkin, Alexey Y.; Scheer, Manfred
Abstract: The coordination chemistry of only Lewis‐base (LB)‐stabilized pnictogenylboranes EH2 BH2 ⋅NMe3 (E=P, As) towards Tl(I) salts has been studied. The reaction of Tl[BAr Cl ] (BAr Cl =[B(3, 5‐C6 H3 Cl2 )4 ] − ) with the corresponding pnictogenylborane results in the formation of [Tl(EH2 BH2 ⋅NMe3 )][BAr Cl ] (1 a : E=P; 1 b : E=As). Whereas the Tl ion in 1 a/b is monocoordinated, the exchange of the weakly coordinating anion (WCA) in the Tl(I) salt leads to the formation of a trigonal pyramidal coordination mode at the Tl atom by coordination of three equivalents of EH2 BH2  ⋅ NMe3 in [Tl(EH2 BH2  ⋅ NMe3 )3 ][WCA] (2 a : E=P, WCA=TEF Cl ; 2 b : E=As, WCA=TEF) (TEF=[Al{OC(CF3 )3 }4 ] −, TEF Cl =[Al{(OC(CF3 )2 (CCl3 )}4 ] − ). Furthermore, by using two equivalents of PH2 BH2 ⋅NMe3, a Tl(I)‐mediated P−P coupling takes place in CH2 Cl2 as solvent resulting in [Me3 N⋅BH2 PH2 PHBH2 ⋅NMe3 ][WCA] (WCA=TEF, 3 a ; BAr Cl, 3 b ; TEF Cl, 3 c ). In contrast, for the arsenic derivatives 1 b and 2 b, no coupling reaction is observed. The underlying chemical processes are elucidated by quantum chemical computations. Abstract : Reactions of NMe3 ‐stabilized pnictogenylboranes with Tl(I) salts of weakly coordinating anions led to rare examples of Tl coordination compounds [Tl(EH2 BH2 ⋅NMe3 ) n ] + ( n =1, 3; E=P, As) featuring mono and threefold coordination of pnictogenylboranes. In addition, by using CH2 Cl2 as a solvent, an unprecedented, Tl‐promoted P−P coupling was observed, leading to [Me3 N⋅BH2 PH2 ‐PHBH2 ⋅NMe3 ] + . During these investigations, novel Tl[WCA] salts were prepared and the synthesis of EH2 BH2 ⋅NMe3 was improved towards greater accessibility.